Poligami Perspektif Fikih Islam dan Tarjih Muhammadiyah - Muhammad Saleh; Siti Risnawati Basri; Megawati Megawati (Al-Azhar Islamic Law Review, 2022)
AbstractBasically, the principle of marriage is monogamy, which is done only once in a lifetime and only consists of one wife and one husband. However, in reality there are some people who are married more than once and have more than one wife which is known as polygamy. The reasons for people who practice polygamy themselves are different, as well as the response of the surrounding community in responding to the practice of polygamy. There are those who support the practice of polygamy, but there are also those who think that polygamy is a form of oppression of women. Seeing the background of the problem as well as the pros and cons of this polygamy polemic, the question arises, how is the law of polygamy in the perspective of Islamic fiqh and Muhammadiyah tarjih.The aim of this research is to know and understand the law of polygamy according to Islamic jurisprudence and Tarjih Muhammadiyah. This research itself is included in the type of library research, which is a type of research that emphasizes research on literatures related to the object being analyzed. Using descriptive analysis method, which is a method used for data that has been collected and then compiled, explained and analyzed. The presentation of the data that has been obtained from the field and from the library is then analyzed to a conclusion.Based on the research that has been done, that polygamy in Islamic jurisprudence is something that is allowed on the condition that the husband is able to treat his wives fairly. Whereas in Muhammadiyah tarjih, polygamy is something that can be done, but is not recommended. This polygamy is also permitted for social emergencies, not only for individual emergencies.Keywords: Polygamy, Islamic law, tarjih Muhammadiyah.